2015
DOI: 10.1159/000430379
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Effect of the Benzene Metabolite Hydroquinone is Mediated by the Modulation of MDR1 Expression via the NF-κB Signaling Pathway

Abstract: This is an Open Access article licensed under the terms of the Creative Commons AttributionNonCommercial 3.0 Unported license (CC BY-NC) (www.karger.com/OA-license), applicable to the online version of the article only. Distribution permitted for non-commercial purposes only. Key Words Hydroquinone • MDR1 • NF-κB Abstract:Background/Aims: Benzene is a toxic chemical whose leukemogenic effects have been studied for decades. The mechanisms of benzene-induced toxicity and leukemogenicity are not fully understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…HQ may cause oxidative stress, DNA damage, cell cycle regulation, apoptosis, and also increased carcinogenic risk [16,17]. Thus, we analyzed whether UVB-irradiated dA may activate the caspase-3 in Detroit 551 cells.…”
Section: Resultsmentioning
confidence: 99%
“…HQ may cause oxidative stress, DNA damage, cell cycle regulation, apoptosis, and also increased carcinogenic risk [16,17]. Thus, we analyzed whether UVB-irradiated dA may activate the caspase-3 in Detroit 551 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Based on epidemiological studies, human exposed to high levels of benzene show an increased risk to develop several acute and chronic diseases, such as acute myeloid leukemia, acute and chronic lymphocytic leukemia, non-Hodgkin lymphoma, multiple myeloma and aplastic anaemia [2] . Moreover, exposure to low doses of benzene has been linked to increased incidence of myelodisplastic syndrome and decreased resistance to infection [3] , which may be explained by its immunotoxic activity targeting mainly T-cells [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that different doses of HQ may induce apoptosis ( 24 , 25 ). Treatment with a low dose of HQ for 24 h induced HQ-mediated apoptosis in murine fetal livers and bone marrow hematopoietic cells ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with a low dose of HQ for 24 h induced HQ-mediated apoptosis in murine fetal livers and bone marrow hematopoietic cells ( 24 ). Treatment with a high dose of HQ for 24 h promoted apoptosis in bone marrow-derived mesenchymal stem cells ( 25 ). Treatment with 50 or 100 µM HQ for 14 h promoted apoptosis in W7.2 rfau cells ( 26 ).…”
Section: Discussionmentioning
confidence: 99%